Evaluation of the Use of the iPosyandu Bidan Application as Integration of Mobile Health and Mobile Learning - Susanti, Ari Indra; Nuraini, Annisa; Darmawan, Flora Honey (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Currently, midwifery services are strengthened by the use of various technologies, so midwives are required to be able to use smartphone-based applications (mobile Health) in recording and reporting Maternal and Child Health (MCH) data and improving lifelong competency based on applications (mobile Learning). This community service activity aims to strengthen midwives' abilities in digital literacy based on the midwife's iPosyandu application to improve MCH services. The method of implementing the activity is in the form of training in the use of the iPosyandu Bidan application. The results of the evaluation of this activity were that most midwives were able to use the midwife's iPosyandu application by quickly learning to input data (mean>5.57) and search for midwifery information (mean>5.65) to improve competence (mean>5.68), and provide health services (mean>5.52). Midwives have good digital literacy when using the Bidan applications such as mHealth and mLearning. Recommendations for the next community service activity are that midwives can provide health services in the form of health education to patients based on the iPosyandu Bidan application.